Risk factors and outcomes, a case series of ischemic stroke in children - Shirley L. Anggriawan; lrawan Mangunatmadja; Djajadiman Gatot; Sofyan lsmael; Najib Advani (Paediatrica Indonesiana, 2009)
Ischemic strokes in children, although generallyrare events, are more prevalent  than  commonlybelieved. Ischemic stroke in children have  beenassociated with coagulation disorders, cardiacanomalies, infections  and  trauma.